Dietary fiber and prebiotics and the gastrointestinal microbiota. (4th March 2017) - Holscher, Hannah D.
ABSTRACT: The gastrointestinal microbiota has an important role in human health, and there is increasing interest in utilizing dietary approaches to modulate the composition and metabolic function of the microbial communities that colonize the gastrointestinal tract to improve health, and prevent or treat disease. One dietary strategy for modulating the microbiota is consumption of dietary fiber and prebiotics that can be metabolized by microbes in the gastrointestinal tract. Human alimentary enzymes are not able to digest most complex carbohydrates and plant polysaccharides. Instead, these polysaccharides are metabolized by microbes which generate short-chain fatty acids (SCFAs), including acetate, propionate, and butyrate. This article reviews the current knowledge of the impact of fiber and prebiotic consumption on the composition and metabolic function of the human gastrointestinal microbiota, including the effects of physiochemical properties of complex carbohydrates, adequate intake and treatment dosages, and the phenotypic responses related to the composition of the human microbiota.